Pendeteksi Keberadaan Orang Asing Menggunakan Face Recognition dan Motion Detection - Peling, Ida Bagus Adisimakrisna; Ariawan, Made Pasek Agus; Subiksa, Gde Brahupadhya; Wiguna, I Komang Arya Ganda (Jurnal Bangkit Indonesia, 2024)
In this modern era, security activities such as siskamling are rarely seen. Something new is needed to replace this old security activity. Technology such as CCTV is one tool that can be used. CCTV can be used, but has some drawbacks. The deficiencies in question include the inability to detect suspicious activity in real time, as well as a 24-hour recording output in the form of video which can lead to wasted storage. Based on these problems, researchers took the initiative to develop a system for detecting the presence of strangers using face recognition and motion detection. The developed system will detect the presence of strangers by detecting the person's movements and matching them with the registered face database. If the face is not registered, the system will start recording and send notifocation to telegram.